Structured Hypergraphs in Cellular Mobile Communication Systems - Ganesan, Ashwin (Association for Computing Machinery, 2023)
An open problem is to extend the results in the literature on unit disk graphs to hypergraph models. Motivated by recent results that the worst-case performance of the distributed maximal scheduling algorithm is characterized by the interference degree of the hypergraph, in the present work we investigate properties of the interference degree of the hypergraph and the structure of hypergraphs arising from physical constraints. We show that the problem of computing the interference degree of a hypergraph is NP-hard and we prove some properties and results concerning this hypergraph invariant. We then investigate which hypergraphs are realizable, i.e. which hypergraphs arise in practice, based on physical constraints, as the interference model of a wireless network. In particular, given the results on the worst-case performance of the maximal scheduling algorithm, a question that arises naturally is: what is the maximal value of r such that the hypergraph K1,r is realizable? We show that this value is r = 4.
uGDX
Keywords: Cellular systems; hypergraph models; unit disk graphs; wireless networks; distributed algorithms; maximal scheduling; interference degree.